A new species of Croton (Euphorbiaceae) from rocky outcrops of the Brazilian and Bolivian Pantanal - Sodré, Rodolfo Carneiro; Silva, Marcos José Da (Phytotaxa, 2026)
Croton pantaneiro, a new species from ferruginous rocky outcrops of the Brazilian and Bolivian Pantanal, is described, illustrated, and placed in Croton sect. Geiseleria. It is morphologically similar to C. adenodontus and C. glandulosus, but it differs from both by its pinnate leaf venation, serrulate or crenulate leaf margin, pistillate flowers with pedicels 0.8–1.3 mm long and sepals 1.8−2.7 mm long, uniformly green capsules, and ecarunculate seeds. Information on its distribution, habitat, conservation status, and systematic placement is provided.